THE ROLE OF THE PSYCHOLOGICAL APPROACH IN RAISING CHILDREN - Sotsieva Elmira (Galaxy International Interdisciplinary Research Journal, 2023)
This article covers the issues of organizing classes based on modern educational technologies, the formation of competencies in the process of teacher training, their adaptation to the student’s mental state, and understanding the student’s feelings. It was emphasized that the main goal of teaching literature is to form a perfect personality who understands the feelings of others and thinks independently.